2002
DOI: 10.1089/152308602760598936
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Angiogenesis by Low Energy Laser Irradiation

Abstract: The effect of low energy laser (He-Ne) irradiation (LELI) on the process of angiogenesis in the infarcted rat heart and in the chick chorioallantoic membrane (CAM), as well as the proliferation of endothelial cells in tissue culture, was investigated. Formation of new blood vessels in the infarcted rat heart was monitored by counting proliferating endothelial cells in blood vessels. In the CAM model, defined areas were laser-irradiated or nonirradiated and blood vessel density was recorded in each site in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…The effect of LELI on the formation process of new blood vessels in the infarcted rat heart monitored by counting the proliferation of EC in blood vessels has been established in a recent study [61]. It also seemed that laser therapy stimulated lymphocytes to produce factors that could modulate EC proliferation in vitro [62].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of LELI on the formation process of new blood vessels in the infarcted rat heart monitored by counting the proliferation of EC in blood vessels has been established in a recent study [61]. It also seemed that laser therapy stimulated lymphocytes to produce factors that could modulate EC proliferation in vitro [62].…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Light can penetrate several tissues, including both the scalp and skull, and reach into the brain. Several clinical and preclinical studies have shown that this process can lead to an improved recovery from stroke.…”
Section: Mechanisms Of Tllltmentioning
confidence: 99%
“…10,[35][36][37][38][39] It has been reported that angiogenesis can cause transiently leaky microvessels 35,39 ; therefore, we wanted to determine the effect of TLT alone and in combination with tPA treatment, which is known to cause vascular damage and hemorrhage. We were concerned that TLT might exacerbate thrombolytic-induced ICH.…”
Section: Figurementioning
confidence: 99%